The political undertones of building national health research systems - reflections from The Gambia - Bloch Paul; Anya Samuel E; Palmer Ayo (BMC, 2009)
Abstract In developing countries building national health research systems is a movement similar to a political leadership contest. Increasingly, political campaigns to select leaders depend less on ideologies and political messages and more on promising change that will promptly improve the quality of life of the voters. In this process the benefits and risks of every action and statement made by the candidates are carefully assessed. Approaches currently promoted to strengthen health research within ministries of health in developing countries place emphasis on implementing logical steps towards building national health research systems including developing a national health research policy and strategic plan, conducting a situational analysis of research in the country, setting a national health research agenda, establishing research ethics and scientific committees, and building human and institutional capacity for health research management and conduct. Although these processes have successfully improved the standards of health research in some settings, many developing countries struggle to get the process going. One reason is that this approach does not deal with basic questions posed within a ministry of health, namely, "What is the political benefit of the ministry assuming control of the process?" and "What are the political implications for the ministry if another institution spearheads the process?" Seen from the perspective of non-governmental organizations, academic institutions and donors trying to support the processes of strengthening national health research systems, one of the foremost activities that needs to be undertaken is to analyze the political context of national health research and, on that basis, plan and implement appropriate political health research advocacy initiatives. This includes the development of explicit messages on the political benefits to the leadership in the ministry of health of their role in the conduct, management and dissemination of health research within the country. Civil society organizations, with links to both government and non-governmental organizations, are well placed to play the role of advocates. It is only through broad and active participation of stakeholders that the process of developing effective and sustainable national health research systems will truly become a national movement inspired, led and sustained by ministries of health.